Perception of sleep quality among men using the Brazilian health system in a city in the interior of São Paulo (Research, Society and Development, 2020)
Objective: describe the perception of sleep quality of men’s users of SUS of Bananal – São Paulo/Brazil and its possible association with lifestyle factors and aspects of health. Method: epidemiological observational, sectional research. Sample composed with 370 men, residents of country city of São Paulo state. It was used a structured questionnaire with open and closed questions, with a short version of Self Reporting Questionnaire (SRQ-20). For the date analysis, it was utilized the Statistical Package for the Social Sciences® 21 software. Results: was found 30% of bad sleep perception. After application of the logistics’ regression multiple binary model, presented association to the outcome hobby/recreation (RP= 1,789, IC95%=1,100-2,910); drug use (RP= 2,016, IC95%=1,068-3,806); CMD (RP= 2,413, IC95%=1,251-4,654); hypertension diagnosis (RP= 1,701, IC95%=1,029-2,810); previous diabetes diagnosis (RP= 1,707, IC95%=1,007-2,893); eat small quantity (RP= 1,558, IC95%=1,130-2,148). Conclusion: vulnerabilities were observed, such as low education, unemployment and low income. There was also little search for health prevention and self-care habits, physical inactivity, irregular eating habits, and search for health services for emergencies, factors that reduce sleep quality. With the results presented, it is possible to promote an improvement in the quality of service to men.